2006
DOI: 10.1159/000097130
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorocarbon Suppresses Lipopolysaccharide- and α-Toxin-Induced Interleukin-8 Release from Alveolar Epithelial Cells

Abstract: Background/Aims: Human pulmonary alveolar epithelial (A549) cells release interleukin-8 (IL-8) on stimulation by lipopolysaccharide (LPS) and α-toxin. We hypothesised that the perfluorocarbons (PFCs), perflubron and FC-84, would block stimulation of A549 cells by these toxins. Methods: The levels of IL-8 production in A549 cells were measured following exposure to toxins for 24 h with or without PFC. The amount of IL-8 released from A549 cells was measured by enzyme-linked immunosorbent assay, and the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…One possibility is that a dense, immiscible PFC liquid with a high spreading coefficient could form a physical protective barrier, thus shielding target cells from various proinflammatory mediators as suggested by the cell culture experiments described here. Evidence for this barrier effect is supported by other studies [21,22]. Another mechanism implicated in the biological effects of PFC is related to the fact that PFC is able to partition into the lipid component of cellular membranes and the cytoplasm [23], where PFC can execute its nonspecific cell membrane stabilization by interfering with (1) the interaction between stimulant and receptor, (2) the transmembrane signal transduction, and (3) the transduction of intracellular signaling pathways [23][24][25].…”
Section: Discussionmentioning
confidence: 76%
“…One possibility is that a dense, immiscible PFC liquid with a high spreading coefficient could form a physical protective barrier, thus shielding target cells from various proinflammatory mediators as suggested by the cell culture experiments described here. Evidence for this barrier effect is supported by other studies [21,22]. Another mechanism implicated in the biological effects of PFC is related to the fact that PFC is able to partition into the lipid component of cellular membranes and the cytoplasm [23], where PFC can execute its nonspecific cell membrane stabilization by interfering with (1) the interaction between stimulant and receptor, (2) the transmembrane signal transduction, and (3) the transduction of intracellular signaling pathways [23][24][25].…”
Section: Discussionmentioning
confidence: 76%
“…Transwell experiments (FIGURE 1A) with monolayers of human cell lines have been used to simulate the air-tissue interface present in vivo and to study the effect of PFCs on IL-8 release [80][81][82]. Studies with the A549 cell line have shown that 24-h incubation with PFOB or FC-84 prevents the release of IL-8 after addition of TNF-α, LPS or α-toxin by acting as a physical barrier [80,82].…”
Section: Effect Of Pfcs On Cytokines and Other Markers Of Inflammation:mentioning
confidence: 99%
“…In recent years, the major studies regarding liquid ventilation have focused on animal experiments or in vitro experiments with few clinical trials. Based on these animal studies and cell experiments, liquid ventilation holds promise to improve low pulmonary compliance and gas exchange in addition to reducing pulmonary inflammatory responses, and ultimately improving the prognosis of animals with ARDS (6)(7)(8)(9)(10)(11)(12)(13)(14). However, the results of clinical randomized controlled trials (RCTs) and basic research have produced conflicting results, and the outlook of liquid ventilation has been disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients require endotracheal intubation and positive pressure ventilation (1,2) and account for millions of days spent in intensive care units (5). In recent years, treatments of ALI/ARDS with improved efficacy have been sought, and studies have indicated that liquid ventilation with perfluorocarbon (PFC) compounds is a promising therapeutic approach (6)(7)(8)(9)(10)(11)(12)(13)(14). PFC is of interest for the treatment of ALI/ARDS due to the unique physicochemical properties, such as high solubility for oxygen, and the anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation